Improving the knowledge women of reproductive age about contraception through use of Klik KB - Aryvia, Nabilla Salsa; Hestiyana, Nita; Mahdiyah, Dede; Lathifah, Nur (Ananda - Health & Education Foundation, 2025)
Background: Family planning is a vital public health initiative aimed at enhancing reproductive health and ensuring sustainable population growth. Despite advancements, knowledge gaps persist, particularly in underserved areas, leading to misconceptions about contraceptive methods. Klik KB, a mobile application by BKKBN, has shown potential in improving contraceptive knowledge, yet its utilization remains limited. Objective: This study evaluates the effectiveness of the Klik KB application in improving contraceptive knowledge among women of reproductive age. Method: A pre-experimental one-group pretest-posttest design was employed, involving 30 women aged 15–49 years. Participants completed a structured questionnaire before and after guided use of the Klik KB application. Statistical analysis was performed using the Wilcoxon signed-rank test. Results: The mean knowledge score significantly increased from 80.32 (SD = 11.82) pretest to 88.17 (SD = 8.74) posttest (p = 0.013). The proportion of participants with good knowledge rose from 70% to 93.3%, while no respondents remained in the poor knowledge category after the intervention. Conclusion: The Klik KB application effectively improves contraceptive knowledge among women of reproductive age, highlighting its potential as a digital tool for enhancing reproductive health education and outcomes.